Encyclopedia of the Spanish-American & Philippine-American wars - Keenan, Jerry; ABC-CLIO Information Services (Santa Barbara, Calif. ABC-CLIO, 2001)
This encyclopedia drives students and interested readers to the basic information about the Spanish-American and Philippine-American wars. Essential information like names, dates and summaries of the significant events related to those wars comprises it. To understand the conflicts, Political backgrounds of each country are presented.
Keywords: Spanish-American War, 1898 -- Encyclopedias; Philippines -- History -- Philippine American War, 1899-1902 -- Encyclopedias